CSB interacts with SNM1A and promotes DNA interstrand crosslink processing. - Iyama, T; Lee, S; Berquist, B; Gileadi, O; Bohr, V; Seidman, M; McHugh, P; Wilson, D (2015)
Cockayne syndrome (CS) is a premature aging disorder characterized by photosensitivity, impaired development and multisystem progressive degeneration, and consists of two strict complementation groups, A and B. Using a yeast two-hybrid approach, we identified the 5'-3' exonuclease SNM1A as one of four strong interacting partners of CSB. This direct interaction was confirmed using purified recombinant proteins-with CSB able to modulate the exonuclease activity of SNM1A on oligonucleotide substrates in vitro-and the two proteins were shown to exist in a common complex in human cell extracts. CSB and SNM1A were also found, using fluorescently tagged proteins in combination with confocal microscopy and laser microirradiation, to be recruited to localized trioxsalen-induced ICL damage in human cells, with accumulation being suppressed by transcription inhibition. Moreover, SNM1A recruitment was significantly reduced in CSB-deficient cells, suggesting coordination between the two proteins in vivo. CSB-deficient neural cells exhibited increased sensitivity to DNA crosslinking agents, particularly, in a non-cycling, differentiated state, as well as delayed ICL processing as revealed by a modified Comet assay and γ-H2AX foci persistence. The results indicate that CSB coordinates the resolution of ICLs, possibly in a transcription-associated repair mechanism involving SNM1A, and that defects in the process could contribute to the post-mitotic degenerative pathologies associated with CS.